Calculus one and several variables - Salas, Saturnino L.; Hille, Einar; Etgen, Garret (John Wiley & Sons, Inc., 2007)
"For ten editions, readers have turned to Salas to learn the difficult concepts of calculus without sacrificing rigor. The book consistently provides clear calculus content to help them master these concepts and understand its relevance to the real world. Throughout the pages, it offers a perfect balance of theory and applications to elevate their mathematical insights. Readers will also find that the book emphasizes both problem-solving skills and real-world applications."--Pub. desc